Lineament Mapping of Jabal Arkenu in Southern Libya - Afkareen , Mohammed. M.; Zamot , Jamal. A.; Al Alwani, Ragab. M. (Scientific Journal of University of Benghazi, 2022)
Remote sensing technology is an important technique in studying perilously and hard-to-reach places for investigating them in the field. Furthermore, it provides fast and accurate data to characterize natural features or physical objects on the ground. Remote sensing data could be used with other approaches to provide a more comprehensive overview of the feature of interest. Accordingly, in this study, the linear features of Jabal Arkenu, in the Kufrah Basin, south of Libya, were studied remotely. The main source data is a satellite image produced from the Alos Palsar satellite, which has a spatial resolution of 12.5 meters. The lineament features map of Jabal Arkenu was created by analyzing several shadow relief images. The length, density, direction and intersection of the lineaments have been extracted from the lineaments map and compared to provide clear maps for determining the type of faults, structural relationships and the geology in the study area. Additionally, the central part of Jabal Arkenu is dominated by high to very high lineament density, while the greater part of the study area is characterized by medium to low lineament density. The dominant direction of the analyzed lineaments is in the northeast direction, and they are concentrated in the north and south parts. Some linear features exist as a boundary between Nepheline syenite with Cambrian Sandstone and Phonolite with Syenite granite.